Spatial administration and legal aspects of the Belt and Road Initiative: Innovative solutions for Armenia - Sos Khachikyan; Jiang Hongzhen (OrdnungsPolitisches Portal (OPO), 2022)
The architecture of public policy through spatial principles has important features in the age of globalization. In this context, the Belt and Road Initiative can be considered as a worldwide public policy project, where conceptual thinking and legal understanding should be discussed. Soft and hard lows - as political and legal aspects, have important feature on the BRI implementation. Flexibility, openness, and inclusiveness are the main soft tools for Belt and Road Initiative participating countries. Based on these, networking and spatial particularities may generate new administrative principles for the BRI project. In this sense, the spatial administration definition was formulated, through which is possible to integrate spatial components of countries that have different social, national, ethnic or religious dimensions, and various geo-economics dimensions. Important to note that Armenia has specific economic and political status in the South Caucasus because of two circumstances. We consider that Belt and Road project is possible to integrate with the Armenian North-South Road Corridor program and free economic zone in Meghri, in order to introduce structural reforms and diversification of economy.
Keywords: 330; Spatial administration; North-South Road Corridor; Belt and Road Initiative; BRI legalaspects; digitalization